2013
DOI: 10.1037/a0031267
|View full text |Cite
|
Sign up to set email alerts
|

Making meaning from collective apologies: Australia's apology to its indigenous peoples.

Abstract: This article considers the meaning of intergroup apologies for their recipients. Our research examined Indigenous people's responses to the 2008 Australian apology to Aboriginal and Torres Strait Islander peoples forcibly removed from their families under previous governments (the Stolen Generations). We interviewed Indigenous men (n = 10) and women (n = 22) about their attitudes toward the apology and forgiveness. To cover the breadth of Indigenous responses to the Australian apology, we sought out participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…Mellor and colleagues note that forgiveness was not a topic that participants engaged with or discussed when thinking of the potential benefits of an apology. Follow‐up research conducted after the apology confirmed that it was the acknowledgment of history contained in the apology and the belief that this might lead to behavior change within the perpetrator group that contributed to the significance of the apology for Indigenous Australians (Philpot, Balvin, Mellor, & Bretherton, 2011).…”
Section: What Are the Outcomes Of The Intergroup Apology? Empirical Fmentioning
confidence: 98%
“…Mellor and colleagues note that forgiveness was not a topic that participants engaged with or discussed when thinking of the potential benefits of an apology. Follow‐up research conducted after the apology confirmed that it was the acknowledgment of history contained in the apology and the belief that this might lead to behavior change within the perpetrator group that contributed to the significance of the apology for Indigenous Australians (Philpot, Balvin, Mellor, & Bretherton, 2011).…”
Section: What Are the Outcomes Of The Intergroup Apology? Empirical Fmentioning
confidence: 98%
“…Indigenous Australian perspectives on the apology and forgiveness show that the apology was not a panacea (Philpot, Balvin, Mellor, & Bretherton, 2013). The Australian apology to the Stolen Generations represents a clearer example of an intergroup apology.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…But the majority of experiments have revealed no effect of collective apologies on intergroup forgiveness (see Hornsey & Wohl, 2013, for a review). The sober conclusions have been reinforced by interview data with victims of intergroup atrocities: Official apologies are often welcomed, but the notion that there is a simple and immediate correspondence between the apology and forgiveness has not emerged (Chapman, 2007;Philpot, Balvin, Mellor, & Bretherton, 2013). The question is, Why would apologies "work" better in terms of promoting forgiveness at the interpersonal level than the collective level?…”
Section: The Tenuous Relationship Between Collective Apologies and Fomentioning
confidence: 93%